Organizational factors affecting successful physician–system integration: A qualitative study of Washington State health executives. Issue 1 (January 2021) - Nguyen, Ann M.; Johnson, Christopher E.; Wood, Suzanne J.; Dowling, William L.
Abstract : Background: Health care delivery is moving toward a value-based environment, which calls for increased integration between physician groups and health systems. Health executives sit at a key nexus point for determining how and when physician–system integration occurs. Purpose: The objective of this study was to identify the organizational factors that health executives perceived to have made physician–system integration successful. Methodology/Approach: We used a multiple-case study research design. We conducted semistructured, qualitative interviews with 25 health executives in the roles of CEO, chief medical officer, chief financial officer and physician group chief executives from eight of Washington State's largest integrated delivery systems. To guide our analysis, we employed open systems theory and Porter's Value Chain to identify physician group and hospital factors that were integral to successful integration. Results: Using the executives' perspectives, the factors grouped into three themes: (1) organizational structure—a mix of integration contracts united by common structural characteristics between physician groups and hospitals); (2) organizational culture—alignment of leadership between physician groups and hospitals; and (3) strategic resources—designated resources to establish and support care coordination activities. Conclusion: Our work indicates that health systems should focus on the pathway to integration success through the alignment of structure (not just the integration contract), culture, and resources and not on an end goal of the physician employment model. Practice Implications: Health system executives are key drivers for when and how physician groups are integrated into health services organizations. This article provides executives with an evidence-based model to aid in formulating integration approaches that combine elements of organizational structure, organizational culture, and strategic resources.